Draft Eleventh Five Year Plan 2007-2012 Annual Plan 2007-2008 Vol-I Government of Madhya Pradesh - Planning Commission (Planning Commission, 2007)
The state now has 9 Commissioner Divisions, 48 Districts, 272 Tehsils and 313 Community Development Blocks, including 89 tribal development blocks. Under three-tier Panchayati Raj, the state has at present 48 Zila Panchayats, 313 Janpad Panchayats and 23,051 Village Panchayats. 14 Municipal Corporations, 86 Municipalities and 237 Nagar Panchayats.
Government of Madhya Pradesh, Planning, Economics and Statistics Department